Livebirth After Uterus Transplantation From a Deceased Donor in a Recipient With Uterine Infertility. Issue 3 (September 2019) - Ejzenberg, D.; Andraus, W.; Carelli Mendes, L.R.B.; Ducatti, L.; Song, A.; Tanigawa, R.; Rocha-Santos, V.; Arantes, R.M.; Soares, J.M.; Serafini, P.C.; de Paiva Haddad, L.B.; Francisco, R.P.; et al.
Abstract : ( Lancet . 2018;392:2697–2704) The first reported successful childbirths after uterus transplant occurred in Sweden in 2013. Since then, only 2 centers (1 in the US and 1 in Sweden) have published reports of livebirths from uterus transplants, with all using live donors. While the use of deceased donors could increase the availability of uterus transplants, one previous transplant from a deceased donor in Turkey resulted in a pregnancy that ended in miscarriage. This report detailed the first reported case of a successful livebirth following a uterus transplant from a deceased donor.